Magnetization transfer in liposome and proteoliposome samples that mimic the protein and lipid composition of myelin. (6th May 2019) - Yang, Weiqi; Lee, Jae‐Seung; Leninger, Maureen; Windschuh, Johannes; Traaseth, Nathaniel J.; Jerschow, Alexej
Abstract : Although magnetization transfer (MT) has been widely used in brain MRI, for example in brain inflammation and multiple sclerosis, the detailed molecular origin of MT effects and the role that proteins play in MT remain unclear. In this work, a proteoliposome model system was used to mimic the myelin environment and to examine the roles of protein, cholesterol, brain cerebrosides, and sphingomyelin embedded in the liposome matrix. Exchange parameters were determined using a double‐quantum filter experiment. The goal was to determine the relative contributions to exchange and MT of cerebrosides, sphingomyelin, cholesterol, and proteins in 1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphocholine bilayers. The main finding was that cerebrosides produced the strongest exchange effects, and that these were even more pronounced than those found for proteins. Sphingomyelin (which also has exchangeable groups at the head of the fatty acid chains, albeit closer to the lipid acyl chains) and cholesterol showed only minimal transfer. Overall, the extracted exchange rates appeared much smaller than commonly assumed for ‐OH and ‐NH groups. Abstract : A proteoliposome model system to mimic the white matter system was used to examine the roles of protein, cholesterol, cerebrosides, and sphingomyelin. Exchange parameters were determined from z‐spectrum experiments. We found that cerebrosides produced the strongest exchange effects, and that these were even more pronounced than those found for proteins.